Application of Magnetometer-Equipped Drone for Mineral Exploration in Mining Operations - Dimitris Perikleous; Katerina Margariti; Pantelis Velanas; Cristina Saez Blazquez; Pedro Carrasco Garcia; Diego Gonzalez-Aguilera (Drones)
This study investigates the geological composition and material distribution within the Lavrion repository located in Greece through an aerial magnetometry survey using a novel aerial drone, CERBERUS, coupled with advanced data processing techniques. The deployment of drone-based magnetometry provided a high-resolution, non-invasive approach to capturing magnetic field data over complex and potentially hazardous terrain (soils highly contaminated), facilitating the rapid and precise mapping of the study area. As a final result, a 3D magnetic susceptibility model was developed, representing a detailed view of the magnetic susceptibility variations within the repository. This model enabled the comprehensive visualization of high-susceptibility zones associated with ferromagnetic materials and low-susceptibility zones correlating with diamagnetic materials like lead, arsenic, cadmium, and zinc. The combined methodologies underscore the effectiveness of drone-based aerial magnetometry in geophysical studies, highlighting its potential for mining exploration and waste management. This study demonstrates that the integration of drone technology with magnetic data processing offers a powerful tool for analysing subsurface structures in a safe, efficient, and non-invasive manner.